Letter from Max Bredig to Marianne and Viktor Homburger, February 17, 1941 - Bredig, Max Albert (1941)
Max Bredig (1902-1977) and Georg Bredig (1868-1968) write a joint letter to Marianne Homburger (1903-1987) and Viktor Homburger (1888-1968), who are interned in the Gurs concentration camp in France. Max provides updates on his new job and family, mentions that he has sent them packages, and that Viktor's children are doing well in England. Georg Bredig express his well-wishes for the family.
Keywords: Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986; Gurs (Concentration camp)